2020
DOI: 10.1016/j.jpeds.2020.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Trends of Diabetic Ketoacidosis in Children and Adolescents with Type 1 Diabetes in British Columbia, Canada

Abstract: To estimate the 11-year incidence trend of diabetic ketoacidosis (DKA) at and after the diagnosis of type 1 diabetes. Study designA retrospective cohort study using a population-based administrative cohort diagnosed with type 1 diabetes at <20 years of age from 2002 to 2012 in British Columbia, Canada. DKA at (1 episode per individual) and DKA after (multiple episodes per individual) the diagnosis of diabetes were defined as DKA occurring ≤14 days or >14 days, respectively, from diagnosis, identified using Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
2
26
0
2
Order By: Relevance
“…We also found divergent temporal trends across age strata, with rising hospitalization rates confined to the youngest and oldest examined age groups. Our finding is corroborated by recent studies that also reported bimodal age distribution for DKA in type 1 diabetics [31,32]. Thus the incidence of type 1 diabetes mellitus, reported to peak in young children and older age groups [33], likely contributed to the increased hospitalization rate of DKA in these age groups.…”
Section: Plos Onesupporting
confidence: 90%
“…We also found divergent temporal trends across age strata, with rising hospitalization rates confined to the youngest and oldest examined age groups. Our finding is corroborated by recent studies that also reported bimodal age distribution for DKA in type 1 diabetics [31,32]. Thus the incidence of type 1 diabetes mellitus, reported to peak in young children and older age groups [33], likely contributed to the increased hospitalization rate of DKA in these age groups.…”
Section: Plos Onesupporting
confidence: 90%
“…Although mortality in children younger than 6 years was low at 0.6%, we had only 16 children within this age category with 1 death reported. A study done by Kao et al on the incidence and trends of DKA in children and adolescents with type 1 diabetes in British Columbia, Canada, reported that younger age at diagnosis (<5 years) was associated with a greater risk of DKA at the time of diabetes diagnosis [ 15 ]. We also did not report any mortality in the ICU which we attributed to close monitoring of patients in the ICU and with a prompt institution of appropriate interventions in the event of clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Even if an episode of DKA is not immediately life‐threatening, it may lead to acute kidney injury 6 or may negatively impact cognitive development of children and adolescents 7,8 . DKA frequently occurs at the time of T1D diagnosis, 9‐11 but also during follow‐up at a rate of 1–10 events per 100 patient‐years, 4,12‐15 which does not only account for considerable morbidity and mortality, but also for substantial health care costs 16‐18 . Whereas the incidence of severe hypoglycemia in T1D has declined over the last years, the rate of DKA in established patients remains stable 10,12,13,19 .…”
Section: Introductionmentioning
confidence: 99%
“…DKA frequently occurs at the time of T1D diagnosis, 9‐11 but also during follow‐up at a rate of 1–10 events per 100 patient‐years, 4,12‐15 which does not only account for considerable morbidity and mortality, but also for substantial health care costs 16‐18 . Whereas the incidence of severe hypoglycemia in T1D has declined over the last years, the rate of DKA in established patients remains stable 10,12,13,19 . Female sex, adolescence, ethnic minority status, low socioeconomic status, an HbA1c level above the target range, and DKA at T1D manifestation are associated with an increased DKA frequency 10,13,20,21 .…”
Section: Introductionmentioning
confidence: 99%